PENINGKATAN KREATIVITAS MASYARAKAT MELALUI PELATIHAN PEMBUATAN POLA DASAR BAJU DI DESA KEDUNGDOWO - Dassucik Dassucik; Dyan Yuliana; Sahwari Sahwari; Ahmad Hafas Rasyidi; Tri Astindari; Agusti Agusti (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Training on making basic patterns of clothing is an activity designed to develop human resources through a series of activities for identification, assessment and a planned learning process. This training activity is expected to make the community more active, innovative, and creative in honing their abilities or potential. The method of implementing this activity is through socialization and training on making basic patterns of clothes for mothers and young women in Kedungdowo Village to have skills in making basic patterns of clothes and increasing community creativity. The result of this activity is the increased creativity of the people of Kedungdowo Village in making basic patterns of clothes and sewing or making fashion products and applying them to themselves and others. Thus, they can open a home-based business by receiving sewing/makeup services, so that they can help the family economy. The expected outcome is the development of business management into independent community activity unit.